Pelatihan Psikoedukasi Art Therapy dengan Menggambar dan Relaksasi Butterfly Hug untuk Mengurangi Kecemasan Akademik dan Mengelola Regulasi Emosi pada Mahasiswa Baru Fakultas Psikologi dan Kesehatan UIN Walisongo Semarang - Dewi Nabela Sofya El-Fikri; Apriya Sani Maulina; Diana Anindita; Afifah Rahmania; Dewi Khurun Aini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
New students often experience academic anxiety due to environmental differences and learning demands. This anxiety is influenced by emotional regulation. This study aims to explore feelings and emotional conflicts while reducing academic anxiety in students using art therapy methods through drawing techniques and butterfly hug relaxation. This study employs the Service Learning (SL) approach. The results, based on pre-test and post-test evaluations, show an improvement in participants' understanding of academic anxiety and emotional regulation. Additionally, participants demonstrated the ability to control their emotions, although they occasionally still experienced academic anxiety. However, they expressed confidence in their ability to overcome it.